Adaptive virtual compliance controller for bilateral teleoperation - Chanuphon Trakarnchaiyo; Abeykoon, A. M. Harsha S.; Manukid Parnichkun; Bohez, Erik L.J.; Royal Thai Government Fellowship (Pathumthani : Asian Institute of Technology)
Since the teleoperation system has been studied throughout many years by several researchers, this system extends the human capacity to manipulate the machine from a distance that benefits for humankind in various fields. Especially, the ability to reflect the sense of touch from the environment to the operator is the most important feature in some teleoperation systems that require the human to feel as if they work at the task site directly. This feature can be attained by using the two-way control or specifically using bilateral control. In this research, the adaptive virtual compliance controller was proposed for bilateral teleoperation for the soft object handling purpose. In details, the guideline of virtual parameter design was given as follow: for the spring stiffness, the value of virtual spring depends on the environment. For soft material grasping, the virtual spring was designed to be softened when touching the object. However, the system should have the high performance when it moves in free motion. Thus, the adaptive spring was design to have the behavior like high rigid spring when it moves in free motion and become soft spring when it contacts with the object. For the other virtual parameters; damping coefficient and inertia, the value of these two parameters was designed based on the concept of vibration suppression with specific cut-off frequencies. For this method, the virtual damping coefficient and inertia will change the value when the virtual stiffness changes in order to maintain the desired cut-off frequencies. The experiment demonstrated the achievement of the proposed bilateral control that improves and enhances the performance of the system for the expected application.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Mechatronics
Thesis (M.Eng.) -- Asian Institute of Technology, 2017